Design of six electrode Enzial electrostatic lens low aberrations for electron gun (Baghdad Science Journal, 2025)
A computerized investigation has been carried out on the design of six electrodes electrostatic lenses used in electron gun application. The Finite-Element Method (FEM) was used in the solution of Laplace equation for determine the axial potential distribution. The electron trajectory under zero magnification condition.The optical properties, spherical and chromatic aberrations, the object and image focal length and object and image position are calculated.A very good futures for the electron gun with these lenses have been computed where are a beam current of 8.7*10-7A can be supplied using cathode tip of radius 10nm.